1873 Nev. Comp. Laws 564 - (:unkn) unknown (My University, 1873)
Offenses Against The Persons of Individuals, § 41: If any person shall assault and beat another with a cowhide, stick, or whip, having at the time, in his possession, a pistol or other deadly weapon, with intent to intimidate and prevent the person assaulted from defending himself, such person shall, on conviction thereof, be imprisoned in the State Prison not less than one or more than ten years.
Keywords: COMMITTING CRIME W/ WEAPON